2018
DOI: 10.1186/s13071-018-2846-0
|View full text |Cite
|
Sign up to set email alerts
|

Malaria infection in mosquitoes decreases the personal protection offered by permethrin-treated bednets

Abstract: BackgroundInsecticides targeting adult mosquitoes are the main way of controlling malaria. They work not only by killing mosquitoes, but also by repelling and irritating them. Indeed their repellent action gives valuable personal protection against biting mosquitoes. In the context of malaria control this personal protection is especially relevant when mosquitoes are infectious, whereas to protect the community we would prefer that the mosquitoes that are not yet infectious are killed (so, not repelled) by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…Journal of Parasitology Research bitten and infected frequently [30,31]. The interference with preference and frequency by a female mosquito to bite noninfected persons and or animals over infected persons may be a game changer as far as decline in active malaria transmission cases is concerned.…”
Section: Introductionmentioning
confidence: 99%
“…Journal of Parasitology Research bitten and infected frequently [30,31]. The interference with preference and frequency by a female mosquito to bite noninfected persons and or animals over infected persons may be a game changer as far as decline in active malaria transmission cases is concerned.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, with a laboratory setting, we recently showed that partially resistant A. arabiensis mosquitoes infected with Plasmodium falciparum sporozoites (the stages of the human malaria parasite that are infectious for human) were no more repelled by permethrin-treated nets [89]. Thus, it suggests that the combination of resistance and malaria infection in mosquitoes may drastically reduce the personal protection ITNs may offer.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, since sporozoites make mosquitoes more motivated to bite [51][52][53][54][55], we might expect that they are less irritated by the insecticide. Indeed, we found in a laboratory experiment that infectious mosquitoes (carrying sporozoites) were less repelled by ITNs [89].…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations